Efforts of the Government and the National Commission on Human Rights in Dealing with the Paniai Case: Problems of the Unfinished Grassroots - Juan Carlos Christfandy Hutahaean; Christian H. J. de Fretes; Suryo Sakti Hadiwijoyo (Universitas Warmadewa, 2024)
This article discusses the roles of the government and the National Commission on Human Rights (Komnas HAM) in handling severe human rights violation cases in Paniai, Papua. The purpose of this article is to determine whether the National Commission on Human Rights handled the severe human rights violations in Paniai optimally. The article employs a qualitative research method as a research procedure that generates descriptive data in the form of written or oral words from individuals or things observed. For gathering information, interviews were used along with different types of literature, like journals, to look at the steps that the National Commission on Human Rights took and news stories from different media outlets about how they dealt with serious human rights violations in Paniai. This article uses the theory of institutional and institutional roles to examine the roles played by the National Commission on Human Rights. The research findings indicate that handling the severe human rights violation cases in Paniai creates problematic situations between the government and civilians. First, the National Commission on Human Rights attempts to adapt to external and social expectations. Second, the formation of an order between the majority and minority in the uniformity pattern of witness elements during the investigation stage conducted by the Attorney General. Other challenges include the back-and-forth return of investigation files, which hinders the process of handling the Paniai case by the National Commission on Human Rights.